Pengaruh Customer Perceived Value, Customer Satisfaction, Dan Product Innovation Terhadap Customer Loyalty (Studi Kasus Rebranding All New Sour Sally) - Faranita Amelia dan Keni (Universitas Tarumanagara, 2019)
This study aims to determine the success of All New Sour Sally rebranding in attracting customer loyalty, which loyalty is seen as one of the important criteria for companies to gain their competitive advantages. The research carries out by taking three independent variables, consisting of customer perceived value, customer satisfaction, and product innovation. This is a descriptive research by using questionnaire which distributed to 167 respondents in Jakarta area. Data was collected by using non probability sampling method. Multiple regression analysis used for data analysis by using SPSS version 23. The findings of the study prove the previous research that each of the three independent variables have significant effect to influence customer loyalty.